Environmental licensing on rhodolith beds: insights from a worm - Santos, Cinthya Simone Gomes (2016)
Rhodoliths are free-living nodules formed by crustose coralline algae that promote multidimensional microhabitats for a highly diverse community. Because their CaCO3 production, rhodolith beds constitute areas of interest for mining activities. On the other hand, other goods and services provided by these environments such as nurseries habitats, fishing and climate regulation remain undersized. Besides directly CaCO3 exploitation, these diverse ecosystems within the Brazilian economic exclusive zone are often covering potentially sites for oil and gas extraction. The IBAMA (Environmental Agency of the Brazilian government) have been applying the precautionary principle to deny requests for oil/gas drilling activities where rhodolith beds occur. Here, we discuss recent data about diversity associated with rhodoliths and also record the "rare" worm Nuchalosyllis cf. maiteae. More than the distribution of one only species, our finding is an emblematic example of our infancy knowledge state about diversity associated with rhodolith beds in southwestern Atlantic. We argue that these knowledge is still insufficient to subside any attempt in classify priorities areas for oil wells drilling. In addition, we claim that the precautionary principle adopted by IBAMA must prevalence until we have robust data allowing predictions concerning higher or lower biodiversity associated with rhodolith beds. (C) 2016 Associacao Brasileira de Ciencia Ecologica e Conservacao. Published by Elsevier Editora Ltda.